-10-3n=-3(n+4)

Simple and best practice solution for -10-3n=-3(n+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10-3n=-3(n+4) equation:



-10-3n=-3(n+4)
We move all terms to the left:
-10-3n-(-3(n+4))=0
We calculate terms in parentheses: -(-3(n+4)), so:
-3(n+4)
We multiply parentheses
-3n-12
Back to the equation:
-(-3n-12)
We get rid of parentheses
-3n+3n+12-10=0
We add all the numbers together, and all the variables
2!=0
There is no solution for this equation

See similar equations:

| 3/10(x+2)=12 | | 2s16=s-25 | | 2w+30=-2(w-7) | | -91=-7(-x+7) | | 10x+22x=5 | | 2t+2t+48=180 | | -x+160=240 | | 10-5v=-5(6v-2) | | x2x+45=8 | | -2x-4(6x-7)=132 | | 2/3w=122 | | 2/5z+7=-13 | | 2(2z+5)=2 | | 33.145d=-123.145 | | 4c-3=14 | | -(15/2)=5y | | (x-2)2=x2-4 | | 7s+3s+40=180 | | 12+x/2=87 | | 5x-3(4x-1)=17 | | 30=6-4y | | 9u-18=2(u+5) | | 7x-(x+5)=6x+5 | | 4x-3(x-2)=21 | | 12x+23=0 | | (x-2)2=x2+4 | | 3b+7=2b+22 | | -32-2x=68 | | -4(-7+7m)+7=-105 | | 3w+2w+45=180 | | 3(4+y)=39 | | 4(0.5x-3)=x-0.25(12-8) |

Equations solver categories